Environmental hyperosmolality regulates phospholipid biosynthesis in the renal epithelial cell line MDCK - Casali, Cecilia Irene (2013)
Hyperosmolality is a key signal for renal physiology. On the one hand, it contributes to the differentiation of renal medullary structures and to the development of the urinary concentrating mechanism. On the other, it is a stress factor. In both cases, hyperosmolality activates processes that require an adequate extension of cellular membranes. In the present work, we examined whether hyperosmolality regulates phospholipid biosynthesis, which is needed for the membrane biogenesis in the renal epithelial cell line Madin-Darby canine kidney (MDCK). Because phospholipids are the structural determinants of all cell membranes, we evaluated their content, synthesis, and regulation in MDCK cultures subjected to different hyperosmotic concentrations of NaCl, urea, or both. Hyperosmolality increased phospholipid content in a concentration-dependent manner. Such an effect was exclusively due to changes in NaCl concentration and occurred at the initial stage of hyperosmolar treatment concomitantly with the expression of the osmoprotective protein COX-2. The hypertonic upregulation of phosphatidylcholine (PC) synthesis, the main constituent of all cell membranes, involved the transcriptional activation of two main regulatory enzymes, choline kinase (CK) and cytidylyltransferase α (CCTα) and required ERK1/2 activation. Considering that physiologically, renal medullary cells are constantly exposed to high and variable NaCl, these findings could contribute to explaining how renal cells could maintain cellular integrity even in a nonfavorable environment.